Viral hepatitis elimination challenges in low‐ and middle‐income countries—Uzbekistan Hepatitis Elimination Program (UHEP). (18th January 2023) - Musabaev, Erkin; Estes, Chris; Sadirova, Shakhlo; Bakieva, Shokhista; Brigida, Krestina; Dunn, Rick; Kottilil, Shyamasundaran; Mathur, Poonam; Abutaleb, Ameer; Razavi‐Shearer, Kathryn; Anstiss, Tim; Yusupaliev, Bakhodir; et al.
Abstract: Background & Aims: Chronic infection with hepatitis B and C viruses (HBV & HCV) is a major contributor to liver disease and liver‐related mortality in Uzbekistan. There is a need to demonstrate the feasibility of large‐scale simplified testing and treatment to implement a national viral hepatitis elimination program. Methods: Thirteen polyclinics were utilized to screen, conduct follow‐up biochemical measures and treat chronic HBV and HCV infection in the general adult population. Task shifting and motivational interviewing training allowed nurses to provide rapid screening and general practitioners (GPs) to treat individuals on‐site. An electronic medical system tracked individuals through the cascade of care. Results: The use of rapid tests allowed for screening of 60 769 people for HCV and HBV over 6 months and permitted outdoor testing during the COVID‐19 pandemic along with COVID testing. 13%–14% of individuals were lost to follow‐up after the rapid test, and another 62%–66% failed to come in for their consultation. One stop testing and treatment did not result in a statistically increase in retention and lack of patient awareness of viral hepatitis was identified as a key factor. Despite training, there were large differences between GPs and patients initiating treatment. Conclusions: The current study demonstrated the feasibility of large‐scale general population screening and task shifting in low‐ and middle‐income countries. However, such programs need to be proceeded by awareness campaign to minimize loss to follow up. In addition, multiple trainings are needed for GPs to bolster their skills to talk to patients about treatment.